Energy conservation using new structured-core and transparent vacuum insulation panels: Numerical simulation with experimental validation. (15th November 2019) - Katsura, Takao; Radwan, Ali; Yang, Zhang; Nakamura, Makoto; Nagano, Katsunori
Highlights: Five distinct structured-core and transparent vacuum insulation panels are analysed. A 3D model is used to predict the insulation ability. VIPs with mesh and frame spacers achieve better insulation performance. The proposed VIPs are cost-effective when compared with silica aerogels and vacuum glazing. VIPs with pillar spacers provide the highest light transparency. Abstract: The rate of heat gain or heat loss from the windows of existing buildings represents a large portion of building energy consumption in harsh hot or cold regions, respectively. Therefore, several thermal insulation technologies have been applied in new buildings. However, these technologies are difficult to implement in existing buildings. Therefore, this study proposes a new, low-cost insulation method using slim, transparent panels with structured cores, for the windows of existing buildings. To do this, five new distinct designs of vacuum insulation panels (VIPs) are proposed to retrofit insulation for the windows of existing buildings. The VIPs comprise a hollow-frame structured-core material encapsulated in a transparent multi-layered polymeric envelope. The effective thermal conductivity of VIPs with different spacers, namely, peek, modified peek, mesh, silica aerogel, and frame, are evaluated at different pressure levels. The spacers are 3D-printed and experimentally-examined. A 3D thermal model is developed and validated using the experimental results of the present work and results from the literature. First, the influences of spacer structure and vacuum pressure on the centre-of-panel thermal conductivity, light transparency, and VIP production costs are evaluated. Second, three different trial manufacturing methods for these VIPs are proposed and compared. Finally, the annual building heat gain and heat loss in two different harsh hot and cold regions, respectively, in Japan are estimated while applying these new proposed VIP designs to the existing windows. The results indicate that VIPs with frame and mesh spacers accomplish better insulation performance, with a centre-of-panel thermal conductivity of 7 × 10 −3 W/m K at a pressure of 1 Pa. Further, the VIP with the peek spacer accomplishes the highest light transparency (0.88). Furthermore, using a frame-type VIP with a total thickness of 3 mm attached to an existing window as a curtain decreases the space heat loss by approximately 69.5%, whereas the light transparency decreases to 75%. In that regard, using a frame-type VIP attached to 3 mm-glass windows decreases window insulation costs by 72% compared with vacuum glazing thermal insulation.